Design and Implementation Six-Steps Inverter Using Fuzzy Sugeno in Permanent Magnet Synchronous Machines - Reza Sarwo Widagdo; Santoso; Izzah Aula Wardah (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2022)
Controlling the speed of the permanent magnet synchronous machines plays an essential role in the industrial process and keeps the permanent magnet synchronous machines running quickly and efficiently. Even if the load changes, the rate speed of the permanent magnet synchronous machines should be adjusted to a constant speed. An excellent permanent magnet synchronous machines speed control system must respond quickly and accurately. However, in practice, rarely find a permanent magnet synchronous machines controlled to achieve a certain speed. This research presents an analysis of fuzzy logic control using seven membership functions for speed control of permanent magnet synchronous machines. Rotor speed control is performed on the rotor voltage by changing the duty cycle value. This voltage change affects the torque of the engine. Adjust the speed by changing the input voltage of the permanent magnet synchronous machines with the six-steps inverter. In the open-loop test (without control), the system cannot reach the desired setting and will only run after input from the throttle. In a closed loop (using fuzzy logic control), the system can achieve the desired setting in 90 seconds even if the setpoint is changed and can move to the setpoint.